2013
DOI: 10.2215/cjn.03640412
|View full text |Cite
|
Sign up to set email alerts
|

Lupus Nephritis

Abstract: SummaryLupus nephritis (LN) increases the morbidity and mortality of patients with SLE. This review compares the randomized, controlled trials that examined various maintenance regimens available to treat LN. Currently, mycophenolate mofetil (MMF) and azathioprine (AZA) are the most popular therapeutic agents used for long-term maintenance of LN. Long-term maintenance with MMF is recommended as the first choice after achieving remission with cyclophosphamide or MMF induction. MMF is effective in consolidating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
0
8
0
2
Order By: Relevance
“…We estimated renal function in our LN patients by using the MDRD eGFR equation, as recommended by Patel et al [10]. Considering that the role of MF in long-term treatment of severe LN remains unsolved [5], we think our results are useful for clinicians.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We estimated renal function in our LN patients by using the MDRD eGFR equation, as recommended by Patel et al [10]. Considering that the role of MF in long-term treatment of severe LN remains unsolved [5], we think our results are useful for clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…The ALMS trial [9], which is an extended study analyzing MF as an induction treatment for LN in 227 patients of different ethnic and geographic origins, found that MMF was superior to AZA with respect to treatment failure and renal relapse (12.9 vs. 23.9%, respectively) [21]. Therefore, it can be concluded that MF should be the first choice in long-term therapy in LN, with slight superiority over AZA [5,22,23,24,25,26]. Although we did not make comparisons with other drugs in the present study, our results indicate a relatively low rate of renal flares using MF (21% at 6 months and 22% at 12 months) and a sustained renal response (68% at 6 months and 71% at 12 months), findings that are closer to those of MAINTAIN [8] than those of ALMS [9], probably because of the ethnicity of the patients included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EC: 2+. -En los pacientes de alto riesgo de presentar recaída (tabla 1), se plantea prolongar el tratamiento durante más de 5 años o incluso de forma indefinida, a menos que haya contraindicación 29 . EC: 4.…”
Section: Figura 1 -Algoritmo Terapéutico De Las Nefritis Lúpicas Tipounclassified
“…Se recomienda que después del tratamiento de inducción, si ha habido respuesta, la dosis de prednisona se sitúe como máximo en 10 mg/día. A partir de este momento, la pauta de descenso debe ser más progresiva e intentar siempre conseguir la más baja posible (5 o menos mg/día) [19][20][21][22] .…”
Section: Clase III Y Ivunclassified